The Civil Responsibility of the Editor of the Electronic Press: Study in Jordanian Legisation - عبد المنعم, الهام حامد (Journal of Legal Sciences, 2019)
This study is intended to discuss the civil responsibility of the editor in the field of electronic publishing.          The purpose of this study is to explain the concept of the editor in the electronic publication and the basis of its civil responsibility, its legal problems under the legal rules contained in the Civil Code.          The first topic deals with the concept and importance of the editor in the news website. The second section deals with the provisions governing the civil responsibility of the editor.